Improving respiratory rate monitoring in general wards following implementation of a rapid response system: a quality improvement initiative - Noriko Sasaki; Yuichi Imanaka; Ayako Tsunemitsu; Osamu Hamada; Takahiko Tsutsumi (BMJ Open Quality)
Background Rapid response systems (RRSs) are widely implemented in hospitals to enhance patient safety. However, the successful activation of RRSs depends on the accurate identification of patient deterioration by ward nurses. Respiratory rate (RR) is a crucial vital sign for early detection of pathological conditions, but it is often neglected or inaccurately recorded. This study aimed to improve RR measurement by nurses in general wards through a quality improvement (QI) project following the implementation of an RRS.Methods A QI project was conducted at a private acute care hospital in Japan from October 2022 to April 2024. The interventions were divided into three phases: (1) public announcements and educational activities, (2) implementation of an early warning system (EWS) and (3) modification of the inter-department handoff template. Interrupted time series analysis was used to evaluate the impact of the interventions on the daily proportion of RR measurements to total vital sign measurements (the total number of RR measurements/the total number of measurements of the traditional four vital signs: blood pressure, heart rate, body temperature and RR).Results A total of 14 864 patients were included in the study. The baseline proportion of RR measurements to total vital sign measurements was approximately 3%. The interventions led to a significant increase in RR measurement. In Phase 1, there was an immediate level change in the proportion of RR measurements to total vital sign measurements (incidence rate ratio (IRR) 1.148; 95% CI 1.075 to 1.226). In Phase 2, there was a further level change (IRR 2.113; 95% CI 1.963 to 2.275) and an increasing slope over time (IRR 1.002; 95% CI 1.002 to 1.003). In Phase 3, there was an additional level change (IRR 1.163; 95% CI 1.103 to 1.227) and an increasing slope (IRR 1.002; 95% CI 1.001 to 1.002).Conclusions A multifaceted approach, including educational activities, EWS integration and modification of inter-department handoff templates, significantly improved RR monitoring in general wards. The findings emphasise the importance of combining immediate educational interventions with long-term strategies such as behavioural nudges to sustain adherence to patient safety protocols.